The comparison of effectivity in breast cancer prevention between skin sparing and subcutaneous mastectomy - 20 years of experience - Berkeš, A; Streit, L; Dražan, L; Veselý, J; Bajus, A; Kubek, T; Šedivý, O; Kanuščák, K; Feiková, K; Strmiska, O; Bohušová, M (Acta chirurgiae plasticae, 2023)
INTRODUCTION: Breast cancer is the leading cause of neoplasm mortality among women. Several prevention strategies have been implemented to early detect and prevent the cancer occurrence. The most effective protocol includes prevention mastectomy for the high-risk patients. In our study, we have compared the efficacy of subcutaneous mastectomy (SCM) and skin sparing mastectomy (SSM) in long-term follow up. METHODS: We have included 201 female patients who have been treated at our department over the course of 20 years between 2000 and 2019. All the patients were at high risk of developing breast cancer and therefore were indicated for the prophylactic mastectomy. The main indication was the presence of the mutation in the BRCA1 or BRCA2 cluster, however, even in the lack of such mutation, the family history was sufficient for the mastectomy indication. Patients underwent either SCM, SSM or areola sparing mastectomy (ASM), and were allocated to aforementioned groups, respectively. We have collected the data regarding the reconstruction method along with age, weight, height, body mass index (BMI) and presence of predisposing genetic mutations such as BRCA positivity. RESULTS: The patients who underwent SSM compared to those who underwent SCM were of higher age, with higher BMI and body mass. The patients in SSM group had statistically significantly higher BMI than in ASM. There was no difference in efficacy between patients who underwent SSM and SCM. The majority of patients (91.5%) were positive for BRCA1 or BRCA2 mutation. In our study, only four patients were tested negative for known breast cancer inducing mutation (three in SCM and one in SSM). The most common reconstruction method was an abdominal flap and breast implant. CONCLUSIONS: Prophylactic mastectomy is a reliable strategy for significantly reducing the number of breast cancer incidence in high-risk patients regardless of the selected method of mastectomy. These operations allow for the subsequent reconstruction with the whole spectrum of reconstructive options.
Keywords: breast cancer; Humans; Mastectomy, Subcutaneous; skin sparing mastectomy; Female; BRCA2; subkutánní mastektomie; lidé; mamoplastika; Breast Neoplasms; mastektomie; ženské pohlaví; Retrospective Studies; Cancer prevention; nádory prsu; retrospektivní studie; Breast cancer; Mastectomy; subcutaneous mastectomy; Mammaplasty